2013
DOI: 10.1593/tlo.13433
|View full text |Cite
|
Sign up to set email alerts
|

Theranostic Gold Nanoparticles Modified for Durable Systemic Circulation Effectively and Safely Enhance the Radiation Therapy of Human Sarcoma Cells and Tumors

Abstract: Radiation therapy (RT) is an integral component of the treatment of many sarcomas and relies on accurate targeting of tumor tissue. Despite conventional treatment planning and RT, local failure rates of 10% to 28% at 5 years have been reported for locally advanced, unresectable sarcomas, due in part to limitations in the cumulative RT dose that may be safely delivered. We describe studies of the potential usefulness of gold nanoparticles modified for durable systemic circulation (through polyethylene glycosyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 45 publications
3
30
0
Order By: Relevance
“…After 24 hours, cells were fixed with 10% neutral buffered formalin (Sigma-Aldrich), nuclei were stained with Hoechst, slides were permeabilized with Triton-X, and cells were immunofluorescently stained for gh2ax as described previously. 36 Finally, fluorescence imaging on samples was performed using a Deltavision Deconvolution microscope (Applied Precision); and foci counting was accomplished using ImageJ as described previously. 36 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 24 hours, cells were fixed with 10% neutral buffered formalin (Sigma-Aldrich), nuclei were stained with Hoechst, slides were permeabilized with Triton-X, and cells were immunofluorescently stained for gh2ax as described previously. 36 Finally, fluorescence imaging on samples was performed using a Deltavision Deconvolution microscope (Applied Precision); and foci counting was accomplished using ImageJ as described previously. 36 …”
Section: Methodsmentioning
confidence: 99%
“…36 Finally, fluorescence imaging on samples was performed using a Deltavision Deconvolution microscope (Applied Precision); and foci counting was accomplished using ImageJ as described previously. 36 …”
Section: Methodsmentioning
confidence: 99%
“…Electron-dense materials such as gold were proven to be suited for this purpose in a series of in vitro and in vivo studies [e.g., (10)(11)(12)(13)(14)(15)]. It is important to point out here that gold NP do not per se alter the cellular radiosensitivity of a tumour.…”
Section: Gold Np As a Microenvironmental Radiation Boostermentioning
confidence: 99%
“…PEG-AuNPs in combination with radiotherapy have enhanced CT imaging whereas radiotherapy has helped to induce tumour tissue damage by increasing unrepaired DNA damage. This study has suggested that AuNPs can potentially improve target imaging and radiosensitization of tumour while minimizing dose to normal tissues thus providing more chances of survival to animals under experimentation (Joh et al 2013). Zhang et al (2015) have prepared high-density CuNPs which have provided fourfold higher signals as PAT contrast agents in NIR region than that of blood.…”
Section: Theranosticsmentioning
confidence: 99%